3D printed milk protein food simulant: Improving the printing performance of milk protein concentration by incorporating whey protein isolate. (October 2018) - Liu, Yaowei; Liu, Dasong; Wei, Guanmian; Ma, Ying; Bhandari, Bhesh; Zhou, Peng
Abstract: This paper aimed to establish a milk protein based 3D printing food simulant and investigated the effect of whey protein isolate (WPI) concentration on the printing performance of milk protein concentrate (MPC). WPI and MPC powders at different ratios were prepared in paste (35 wt%, total dry matter content). The rheological properties and water distribution of protein matrix prepared with different MPC/WPI ratios were characterized with a rheometer and low field nuclear magnetic resonance (LF-NMR), respectively. Moreover, the variations in the microstructure of printed objects were observed with a scanning electron microscope (SEM). The printed objects showed different appearance and physical properties; the printing fidelity was also evaluated by measuring the geometric accuracy of printed objects. The rheological and texture data showed that the presence of WPI could reduce the apparent viscosity and soften the MPC paste, benefiting the printing process. The results showed that the milk powder paste mixture prepared with MPC/WPI at a ratio of 5/2 was the most desirable material for extrusion-based 3D printing, which could be successfully printed and matched the designed 3D model best. Industrial relevance: 3D printing in food sector has been an attractive and emerging technology owing to its potential advantages, such as customized food designs, personalized and digitalized nutrition, simplifying supply chain and so on. This paper established a high protein food simulant for 3D printing, optimized its printing performance with whey protein isolate, and studied the physicochemical property of prepared protein pastes. The overall results indicated that milk protein powders could be the promising materials for the application in food 3D printing. In flowing studies or practical production, the glycerol could be replaced by ingredients such as syrup, honey etc. This study may give more insights into 3D printing applied in food sector and facilitate the further developments of 3D food printing. Highlights: Fabrication of milk protein based 3D printing food simulant was investigated. Milk protein paste with MPC only is too hard to be extruded from printer nozzle. Increasing proportion of WPI would reduce viscosity and soften the protein pastes. Milk protein paste with MPC/WPI at ratio of 5/2 exhibits good printing performance.